FAMILY INSTITUTION AS A MICROCOMMUNITY (Web of Teachers: Inderscience Research, 2025)
This article explores the social characteristics of the family institution and classifies its functions. The family institution is a microcommunity. It is precisely this aspect that prompts the exploration of its modern social functions. Social characteristics and social functions can be distinguished from an etymological point of view; however, such an approach would require not a social-philosophical, but rather a linguistic and morphological approach. Therefore, in this article, social characteristics and functions are viewed as realities in dialectical harmony.